Pengaruh Lingkungan Kerja dan Kompensasi Terhadap Kepausan Kerja Serta Dampaknya Pada Kinerja Karyawan di PT. Jatisari Sri Rejeki - Nurhayati Saragih; Agustina Massora (Fakultas Ekonomi Universitas Borobudur, 2021)
This study aims to examine and analyze the influence of factors related to EmployeePerformance. These factors include Work Environment and Compensation, which subsequentlyfunctioned as independent variables which influence Employee Performance as a dependentvariable, while Job Satisfaction is a variable that functions as an Intervening variable. Theresearch method used in this study is path analysis.Research results show that there is a direct influence of work environment andcompensation on job satisfaction. work environment, compensation and job satisfaction have adirect effect on employee performance. Job satisfaction as an intervening variable is able tomediate the indirect influence of work environment and compensation on employee performance,with the results of the suitability test of a decent model.Keywords: work environment, compensation, job satisfaction, employee performance Discipline,Work Environment, Employee Performance, and Employee Productivity